Bismuth ferrite-based lead-free ceramics and multilayers with high recoverable energy density. Issue 9 (15th February 2018) - Wang, Dawei; Fan, Zhongming; Zhou, Di; Khesro, Amir; Murakami, Shunsuke; Feteira, Antonio; Zhao, Quanliang; Tan, Xiaoli; Reaney, Ian M.
Abstract : Bismuth ferrite-based lead-free multilayers with a high recoverable energy density of 6.74 J cm −3 and an efficiency of 77%, stable up to 125 °C. Abstract : Lead-free ceramics with high recoverable energy density ( W rec ) and energy storage efficiency ( η ) are attractive for advanced pulsed power capacitors to enable greater miniaturization and integration. In this work, dense bismuth ferrite (BF)-based, lead-free 0.75(Bi1− x Nd x )FeO3 -0.25BaTiO3 (BN x F-BT) ceramics and multilayers were fabricated. A transition from a mixed pseudocubic and R 3 c to a purely pseudocubic structure was observed as x increased with the optimum properties obtained for mixed compositions. The highest energy densities, W ∼ 4.1 J cm −3 and W rec ∼ 1.82 J cm −3, were achieved for BN15F-BT, due to the enhanced breakdown field strength (BDS ∼ 180 kV cm −1 ) and large maximum polarization ( P max ∼ 40 μC cm −2 ). The multilayers of this composition possessed both a high W rec of 6.74 J cm −3 and η of 77% and were stable up to 125 °C. Nd doped BF-based ceramics with enhanced BDS and large W rec are therefore considered promising candidates for lead-free energy storage applications.